Orientalization of Gaming A Postcolonial Study of Call of Duty Modern Warfare - Naser Janani; Mohammad Fallah; Ali Zeraatpisheh (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Call of Duty is a popular first-person shooter (FPS) game. Call of Duty: Modern Warfare (2007) was the first game in the franchise which did not focus on the World Wars’ history. It was also the first Call of Duty which had a continuous interactive digital narrative (IDN). This article attempts to take a comparative approach to the game. As a cultural product, the game is susceptible to postcolonial and Orientalist discourses. This article attempts to apply Edward Wadie Said’s theories to Call of Duty: Modern Warfare in order to prove that the game’s IDN was shaped by postcolonialism and Orientalism. The game functioned as a cultural medium which disseminated Orientalist discourses amongst its player base. As such, this article tries to not only shed light upon a lesser-known aspect of Call of Duty: Modern Warfare but also to demonstrate that computer games are not exempt from external cultural forces.